Sex-biased parasitism and expression of a sexual signal. (16th November 2020) - Rosso, Adam A; Nicholson, Daniel J; Logan, Michael L; Chung, Albert K; Curlis, John David; Degon, Zachariah M; Knell, Robert J; Garner, Trenton W J; McMillan, W Owen; Cox, Christian L
Abstract: Given that sexual signals are often expressed more highly in one sex than the other, they can impose a sex-specific cost of reproduction through parasitism. The two primary paradigms regarding the relationship of parasites to sexual signals are the good genes hypothesis and the immunocompetence handicap hypothesis; however, there are other ecological, morphological and energetic factors that might influence parasite infections in a sex-specific fashion. We tested the relationship between expression of a sexual signal (the dewlap) and ecological, morphological and energetic factors mediating ectoparasite (mite) load between male and female Panamanian slender anoles ( Anolis apletophallus ). We found that males were more highly parasitized than females because of the preponderance of ectoparasites on the larger dewlap of males. Indeed, ectoparasite infection increased with both body size and dewlap size in males but not in females, and parasite infection was related to energy storage in a sex-specific fashion for the fat bodies, liver and gonads. Our work and previous work on testosterone in anoles suggests that this pattern did not arise solely from immunosuppression by testosterone, but that mites prefer the dewlap as an attachment site. Thus, the expression of this sexual signal could incur a fitness cost that might structure life-history trade-offs.